2020
DOI: 10.3390/plants9010122
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Digestive Enzymes and Antioxidant Activity of Extracts from Fruits of Cornus alba, Cornus sanguinea subsp. hungarica and Cornus florida–A Comparative Study

Abstract: The fruits of some Cornus species (dogwoods) are used in traditional medicine and considered potential anti-diabetic and hypolipemic agents. The aim of the study was to determine the ability of extracts from Cornus alba (CA), Cornus florida (CF), and Cornus sanguinea (CS) to inhibit digestive enzymes namely α-amylase, pancreatic lipase, and α-glucosidase, as well as isolation of compounds from plant material with the strongest effect. In addition, the phytochemical profile and antioxidant activity of extracts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 35 publications
1
18
1
Order By: Relevance
“…Suprisingly, α-glucosidase activity increased in the presence of FME at 12.5, 25, 50 and 100 µg/ml. On the contrary of our work, Truba et al reported that aqueous-ethanolic extract of C. sanguinea fruit exhibited inhibitory effect against α-glucosidase enzyme and the IC50 value of it was determined as 70.07 ± 16.62 µg/ml [25]. In this study, the results of in vitro AChE inhibitory potentials of the extracts showed that LME showed higher inhibitory effects that of FME but it had lower inhibitory action than galantamine.…”
Section: Discussioncontrasting
confidence: 87%
“…Suprisingly, α-glucosidase activity increased in the presence of FME at 12.5, 25, 50 and 100 µg/ml. On the contrary of our work, Truba et al reported that aqueous-ethanolic extract of C. sanguinea fruit exhibited inhibitory effect against α-glucosidase enzyme and the IC50 value of it was determined as 70.07 ± 16.62 µg/ml [25]. In this study, the results of in vitro AChE inhibitory potentials of the extracts showed that LME showed higher inhibitory effects that of FME but it had lower inhibitory action than galantamine.…”
Section: Discussioncontrasting
confidence: 87%
“…However, no studies on the isolation of the secondary metabolites from these drupes have been provided so far; thus, both the existing findings indicating dogberries as a potential source of natural antioxidants and our ongoing studies on small Italian fruits [13] aimed to fully investigate the chemical constituents of C. sanguinea fruits. New compounds, including a flavonol glycoside (1), a megastigmane (2), 2 uncommon cyclohexylethanoids (3,4), and a phenylethanol derivative (5), together with 15 known compounds (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), have been isolated and characterized in our work.…”
mentioning
confidence: 99%
“…Moreover, the fruits and leaves have antibacterial and antiseptic properties and are used to treat wounds and/or against pathogens [8]. Preliminary phytochemical studies on the chemical content of common dogwood drupes have revealed the occurrence of flavonoids, especially as glycosides of quercetin, isorhamnetin, and myricetin [9,10], which could contribute to the free radical scavenging and H 2 O 2 inhibiting activity as reported in the literature [11,12]. However, no studies on the isolation of the secondary metabolites from these drupes have been provided so far; thus, both the existing findings indicating dogberries as a potential source of natural antioxidants and our ongoing studies on small Italian fruits [13] aimed to fully investigate the chemical constituents of C. sanguinea fruits.…”
mentioning
confidence: 99%
“…Plants are an important biological resource and contain many compounds that play an important role in metabolic disorders [ 34 ]. Owing to their biodegradability and low toxicity, plant-derived compounds are widely used in the development of biological pesticides.…”
Section: Discussionmentioning
confidence: 99%